Comparison of preoperative chemotherapy using docetaxel, cisplatin and fluorouracil with cisplatin and fluorouracil in patients with advanced carcinoma of the thoracic esophagus. Issue 2 (17th February 2014) - Ui, T.; Fujii, H.; Hosoya, Y.; Nagase, M.; Mieno, M. N.; Mori, M.; Zuiki, T.; Saito, S.; Kurashina, K.; Haruta, H.; Matsumoto, S.; Niki, T.; et al.
Summary We retrospectively compared preoperative docetaxel, cisplatin, and fluorouracil (DCF) with cisplatin and fluorouracil (CF) in patients with esophageal cancer. The study included patients with advanced thoracic esophageal carcinoma (excluding T4 tumors) receiving preoperative chemotherapy. In the DCF group, five patients received two courses of treatment every 4 weeks, and 33 patients received three courses every 3 weeks. In the CF group, 38 patients received two courses of treatment every 4 weeks. Patients underwent curative surgery 4–5 weeks after completing chemotherapy. Patient demographic characteristics did not differ between the two study groups. The incidence of a grade 3 or 4 hematologic toxicity was significantly higher in the DCF group (33 patients) than in the CF group (five patients; P < 0.001). Curative resection was accomplished in 79% of patients in the DCF group and 66% in the CF group (P = 0.305). There were no in‐hospital deaths. The incidence of perioperative complications did not differ between the groups. A grade 2 or 3 histological response was attained in a significantly higher proportion of patients in the DCF group (63%) than in the CF group (5%; P < 0.001). Progression‐free survival and overall survival were significantly higher in the DCF group (P = 0.013, hazard ratio 0.473; P = 0.001, hazard ratio 0.344). In conclusion, a grade 3 or 4 hematologic toxicity was common in the DCF group but was managed by supportive therapy. Histological response rate, progression‐free survival, and overall survival were significantly higher in the DCF group compared with the CF group.